The Effects of Trait Emotional Intelligence on Adolescent Substance Use: Findings From a Hungarian Representative Survey - Kun, Bernadette; Urbán, Róbert; Paksi, Borbála; Griffiths, Mark D.; Richman, Mara J.; Demetrovics, Zsolt (Frontiers in Psychiatry, 2019)
Previous research has emphasized the importance of emotions in the development of adult and adolescent substance use. There is substantial evidence for deficits in emotional processing among teenagers with substance use, but few studies have investigated the association between emotional intelligence and adolescent substance use. The aim of the present study was to examine the relationship between the use of tobacco, alcohol, and illicit drugs and level of emotional intelligence among adolescents. A representative sample of high school students participated in the study (N=2380). Substance use patterns were assessed using data from the ESPAD Survey, and emotional intelligence was assessed with the Bar-On Emotional Quotient Inventory Youth Version. Self-esteem and depressive symptomatology were also assessed to compare their effects on the frequency of substance use with the effect of emotional intelligence. Results demonstrated that greater difficulty in stress management and empathy predicted a higher frequency of tobacco, alcohol and cannabis use. However, the level of emotional intelligence showed only a weak relationship to substance use habits. Latent profile analyses supported the hypothesis that different emotional patterns and problems underlie different types of psychoactive substances. Using a multiple linear regression model, the present study found that although emotional intelligence is not a key factor underlying substance use habits, it has an individual effect on substance use beyond depressive tendencies and self-esteem. These results can be applied to both drug prevention programs and interventions in substance abuse treatment.